'A pretty kettle of fish': United Nations assistance in the mass dismissal of labor in the Iranian oil industry, 1959–1960. (2nd January 2019) - Muschik, Eva-Maria
ABSTRACT: This article examines the assignment of John Alexander-Sinclair, a British United Nations (UN) development expert, in Iran. In the late 1960s, Alexander-Sinclair was invited to arrange the 'redeployment' of 20, 000 allegedly redundant oil workers and mediate between the consortium of European and American companies, which was in de facto control of the country's oil industry, and the state-led National Iranian Oil Company, which was nominally in charge. His UN mission enabled the cooperation between Iranian officials and foreign companies, which eventually led to the severance of workers on a massive scale. Much of the existing scholarly work on the history of international organizations and labor has focused on the role of the former in advocating international norms to improve the lives of workers across the globe. This article, by contrast, examines the use of UN assistance as a means to circumvent workers' existing protections and benefits. Second, the notion of a 'rule of experts, ' which suggests that development practitioners gained unprecedented powers after World War II, dominates much of the secondary literature. By showing how the UN representative in Iran appeared as a rather impotent pawn in the politics of local interest groups, the article demonstrates the limits of this argument.